Parathethys Last Gasp in Central Asia and Late Oligocene Accelerated Uplift of the Pamirs. Issue 21 (15th October 2019) - Wang, Xin; Carrapa, Barbara; Chapman, James B.; Henriquez, Susana; Wang, Mi; DeCelles, Peter G.; Li, Zaijun; Wang, Fei; Oimuhammadzoda, Ilhomjon; Gadoev, Mustafo; Chen, Fahu
Abstract: Cenozoic sedimentary rocks in the Tajik Basin record the history of retreat of the Paratethys from central Asia, tectonic activity within the surrounding Pamir and Tian Shan mountains, and Asian aridification. However, there remains a paucity of precise chronological constraints on the sequences from this region. Here we present integrated magnetostratigraphic, detrital zircon and monazite U‐Pb geochronologic, and detrital apatite fission track thermochronologic data from the lower Cenozoic sedimentary sequences in the Tajik Basin. Our results indicate that the investigated sedimentary rocks were deposited between ~41 and 23.3 Ma, with a depositional hiatus between ~36 and 31 Ma. The last two marine regressions were dated at ~41 and ~37.4 Ma, respectively. Eolian sandy loess dominates the sequences from ~31 to ~25 Ma and gradually transitions to fluvial facies after ~25 Ma, consistent with late Oligocene to early Miocene acceleration of active deformation, uplift, and exhumation of the Pamirs. Plain Language Summary: Central Asia has experienced prolonged climatic changes, from a relatively hot and humid climate, influenced by the Paratethys, to an extremely dry continental climate, during the Cenozoic. Precise chronological constraints on the sedimentary sequences that record this transition are required for resolving the forcing mechanisms behind this significant paleoclimate change. We report a reliable chronological framework for the lower Cenozoic sedimentary record in the Tajik Basin, which was occupied by the Paratethys during the early Cenozoic and a foreland basin related to uplift of the Pamir‐Tian Shan orogen. Our new data help advance scientific understanding of the sea retreat, mountain building, and long‐term climate changes in central Asia during the early Cenozoic. Key Points: We report the first high‐resolution magnetostratigraphy of sedimentary sequences in the Tajik Basin spanning from ~23.3 to ~41 Ma The penultimate and ultimate retreat of the Paratethys from central Asia were dated at ~41 and ~37.4 Ma, respectively The Pamir Mountains have experienced active deformation and accelerated exhumation during the late Oligocene to early Miocene (~25 Ma)